PARENTING IMPLEMENTASI KURIKULUM MERDEKA SEBAGAI BUDAYA POSITIF - Ridwan, Ridwan; Lestariningrum, Anik; Iswantiningtyas, Veny; Yulianto, Dema; Al-Fahmi, Sari Nadhifa (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
The aim of this community service activity is to provide assistance to PAUD Flamboyan Gs Campurejo, Kediri City in terms of implementing the independent curriculum in developing positive attitudes, culture and learning. The Independent Curriculum (IKM) is an educational approach that provides freedom in learning to students to enable children to develop their own interests and creativity through activities that are relevant to their daily lives. The method used in this PKM activity is to design the service implementation in three stages, the first is the preparation stage, implementation by distributing questionnaires and presenting parenting material in front of the parent class and the last stage is the evaluation stage and preparing a follow-up plan. The implementation of Community Service activities is packaged using lecture, discussion and individual consultation methods. Parenting activities as a parent class are a routine agenda to help understand how to care for young children and the synergies that can be carried out with educational units. For this reason, the community service program is to provide material that is presented during implementation activities with the concept of lectures on how to develop positive attitudes, culture and learning and efforts that can be made by parents involved in school programs as a way to overcome problems. There are discussions and consultations on children's growth and development.